Fibroblast Growth Factor 2 Enhances Zika Virus Infection in Human Fetal Brain. (13th February 2019) - Limonta, Daniel; Jovel, Juan; Kumar, Anil; Lu, Julia; Hou, Shangmei; Airo, Adriana M; Lopez-Orozco, Joaquin; Wong, Cheung Pang; Saito, Leina; Branton, William; Wong, Gane Ka-Shu; Mason, Andrew; et al.
Abstract: Zika virus (ZIKV) is an emerging pathogen that can cause microcephaly and other neurological defects in developing fetuses. The cellular response to ZIKV in the fetal brain is not well understood. Here, we show that ZIKV infection of human fetal astrocytes (HFAs), the most abundant cell type in the brain, results in elevated expression and secretion of fibroblast growth factor 2 (FGF2). This cytokine was shown to enhance replication and spread of ZIKV in HFAs and human fetal brain explants. The proviral effect of FGF2 is likely mediated in part by suppression of the interferon response, which would represent a novel mechanism by which viruses antagonize host antiviral defenses. We posit that FGF2-enhanced virus replication in the fetal brain contributes to the neurodevelopmental disorders associated with in utero ZIKV infection. As such, targeting FGF2-dependent signaling should be explored further as a strategy to limit replication of ZIKV. Abstract : We show that fibroblast growth factor 2 induced by Zika virus infection enhances viral replication and spread in human fetal astrocytes and brain explants. The proviral effects of this cytokine are likely mediated by suppression of the interferon response.